TECHNIQUES FOR TEACHING TOEFL FOR THE POSTGRADUATE PROGRAM STUDENTS OF IAIN PONOROGO - Ari Amnan (Humaniora Scientia, 2021)
Test of English as a Foreign Language (TOEFL) is an English proficiency test of language skillwhich is as the most well-liked and followed by people in the world. Postgraduate program ofState Islamic Institute (IAIN) of Ponorogo Issued a policy which obligates the students to takelanguage proficiency test (TOEFL) as one of obligatory requirements to pass the thesisexamination. The kind of this research is descriptive qualitative. The result of the research showsthat Techniques used by tutors in the TOEFL preparation class are Drill, Warm-up,Dialogue/Narrative presentation, discussion, and checking. The use of those techniques is tohelp students in understanding the materials.The existence of TOEFL preparation class is veryimportant. Its role as the bridge for students makes it strategic in accompanying students to getthe target of score.Keywords: TOEFL Preparation, Test, Techniques, Teaching